Next-Generation Data Storage: Transistor and Dna - Pusane, Ali E.; Arslan, Şuayb Şefik; Ashrafi, Reza A. (Institute of Electrical and Electronics Engineers Inc., 2018)
With the generation of diverse data growing at exponential rates, investigating better digital storage media is inevitable. Currently, one solution is the utilization of solid-state based memory devices, which offer several desirable characteristics, including very fast write/read operations, scalability, and reduced fabrication costs. However, with the increased need for long term and large storage space, their data retention capabilities drastically decline. Another emerging storage technology on the horizon is the biotechnological based DNA storage, which renders a phenomenal storage capacities. In this paper, basics of these two promising storage technologies are reviewed and their potential future trends are discussed. © 2018 IEEE.
Şefik Şuayb Arslan (MEF Author)
Keywords: Transistor; Phenomenal storage capacities; Data retention capabilities; Write/read operations; Digital storage media; Storage space; Storage technology; Fabrication costs; Generation data storage; Biotechnological based dna storage; Exponential rates; Solid-state based memory devices; SSD Flash Memory; DNA Storage; Channel Model